2009
DOI: 10.7326/0003-4819-151-11-200912010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression in Adults: U.S. Preventive Services Task Force Recommendation Statement

Abstract: The USPSTF recommends screening adults for depression when staff-assisted depression care supports are in place to assure accurate diagnosis, effective treatment, and follow-up. (Grade B recommendation) The USPSTF recommends against routinely screening adults for depression when staff-assisted depression care supports are not in place. There may be considerations that support screening for depression in an individual patient. (Grade C recommendation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(102 citation statements)
references
References 0 publications
1
99
1
1
Order By: Relevance
“…Obesity has been associated with cognitive decline [54] and functional limitations [55], posing additional challenges to diagnosing depression among obese older adults. However, current guideline from the U.S. Preventive Services Task Force [56] on screening for depression does not consider obesity as a risk factor and/or comorbidity of depression. Given the barriers in depression screening in relation to obesity, health care providers should be aware of the potential risk for depression among obese older adults and monitor their mood status.…”
Section: Discussionmentioning
confidence: 96%
“…Obesity has been associated with cognitive decline [54] and functional limitations [55], posing additional challenges to diagnosing depression among obese older adults. However, current guideline from the U.S. Preventive Services Task Force [56] on screening for depression does not consider obesity as a risk factor and/or comorbidity of depression. Given the barriers in depression screening in relation to obesity, health care providers should be aware of the potential risk for depression among obese older adults and monitor their mood status.…”
Section: Discussionmentioning
confidence: 96%
“…Although stigmatization may raise concern that public disclosure of a medical student's depression could compromise a student's status, such concern should not outweigh the importance of providing confidential and robust care for depressed students. In addition to direct clinical care and related screening, 64,65 we believe that preventive and educational interventions are desirable. We argue for a change in medical school culture in which medical students, teachers, administrators, and the entire medical school environment adopt a broad-based preventive approach to dealing with the risk of depression in medical students.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, this study of the prevalence and frequency of cannabis use among primary care patients, in a state with legalized use, found that most primary care patients who completed recommended routine behavioral health screening (e.g., depression and alcohol), 51,52 also completed a question about past-year cannabis use. Additionally, while 15% of all primary care patients reported any past-year cannabis use, the prevalence was much higher in important patient subgroups.…”
Section: Discussionmentioning
confidence: 89%